2005
DOI: 10.1051/0004-6361:20042209
|View full text |Cite
|
Sign up to set email alerts
|

Sidereal orientation of the Earth and stability of the VLBI celestial reference frame

Abstract: Abstract. The consideration of time stability of extragalactic radio sources observed by VLBI is shown to allow the realisation of more consistent celestial reference frames. The impact on the estimation of precession and nutation components is investigated over the time span [1984][1985][1986][1987][1988][1989][1990][1991][1992][1993][1994][1995][1996][1997][1998][1999][2000][2001][2002]. The precession correction to the IAU 2000 value that is obtained when excluding the unstable sources reaches 49 ± 5 µas/ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…At the level of accuracy reached nowadays, these variants can have noticeable consequences on the derived VLBI products (Feissel-Vernier 2003;Feissel-Vernier et al 2005, 2006Lambert & Dehant 2007;Heinkelmann & Tesmer 2013). These options include the choice of the sessions to be analyzed, the exclusion of a part of the data (e.g., because of bad quality), and various aspects relevant to the parameterization (split between global, sessionwise, and arc parameters) and to the constraints (especially those applied globally to the station and radio source coordinates).…”
Section: Data Setsmentioning
confidence: 99%
“…At the level of accuracy reached nowadays, these variants can have noticeable consequences on the derived VLBI products (Feissel-Vernier 2003;Feissel-Vernier et al 2005, 2006Lambert & Dehant 2007;Heinkelmann & Tesmer 2013). These options include the choice of the sessions to be analyzed, the exclusion of a part of the data (e.g., because of bad quality), and various aspects relevant to the parameterization (split between global, sessionwise, and arc parameters) and to the constraints (especially those applied globally to the station and radio source coordinates).…”
Section: Data Setsmentioning
confidence: 99%
“…Some IVS analysis centers have processed the geodetic VLBI observational database to obtain Table 1 is available in electronic form at http://www.aanda.org radio source coordinate time series. These time series represent the motion of the centroid of the radio source as seen by the network, and were intensively used in the past to build up a more stable reference frame (see, e.g., Feissel-Vernier 2003;Feissel-Vernier et al 2005Lambert & Gontier 2009). The selection of the ICRF2 defining sources was partly based on these series (Fey et al 2010): the authors defined a stability criterion and ranked the sources from the most to the less stable.…”
Section: Introductionmentioning
confidence: 99%
“…When the modelled nutation (MHB2000 without the free modes) is subtracted from the observation, the signal associated with the free core nutation is the major source of residuals. From the analysis of those residuals, Feissel-Vernier (2003) and Feissel-Vernier et al (2005) have shown the presence of some power in the FICN frequency band. This motivated us to compute theoretically the nutational response of a three-layer Earth for the normal nutation modes excited by the noise of the atmosphere and/or the ocean at those frequencies.…”
Section: Introductionmentioning
confidence: 99%